Analisis Konsep Manajemen Strategi dalam Perencanaan Pendidikan Islam - Khoirinnisa; Samsul Susilawati (Al-Kindi, 2026)
Strategy formulation is an important component of strategic management that serves to direct Islamic educational institutions in achieving long-term goals effectively and sustainably. This study aims to describe the concept of strategy formulation in Islamic education planning by examining Fred R. David's strategic management framework, which includes the formulation of vision and mission, analysis of the internal and external environment through the SWOT approach, determination of long-term goals based on SMART principles, and strategy selection through the Quantitative Strategic Planning Matrix (QSPM). This research emphasizes three technical stages of strategy formulation, namely the input stage, the Stage Matching and the Decision Stage, which allows strategic decision-making to be carried out systematically, objectively, and measurably. The results of the analysis show that the formulation of the strategy not only clarifies the direction of education policy, but also increases the effectiveness of governance, competitiveness, and adaptability of Islamic educational institutions to environmental changes. The integration of Islamic values in the strategy formulation process also strengthens the character of the institution, so that the resulting strategy is not only managerial, but also reflects moral and spiritual principles. Thus, strategy formulation is an important instrument in realizing Islamic educational institutions that are superior, responsive, and oriented towards sustainable quality improvement.